The model of formation of system multiprofessional competencies of future professionals for sustainable development - Koklevsky, Alexander V. (Journal of the Belarusian State University. Journalism, 2019)
The article presents a model of multiprofessional competencies of future professionals for sustainable development. The content of the model blocks: concept, target, content-methodological, executive and corrective and effective. Content block conceptual model is presented on three levels of methodological analysis: the general philosophical, general scientific and specific scientific. Based on the provisions of the methodological approaches conceptual model unit, sets out the principles that define the requirements for the formation of the system organization multiprofessional competencies of future professionals for sustainable development. The mechanism of formation of the organization multiprofessional competencies of future professionals for sustainable development through the introduction of the model developed in the educational process through the creation and implementation of psychological and pedagogical conditions.